Research on the behavioral choices of merchants, logistics enterprises and consumers participating in the recycling of excessive packaging for e-tailing goods - Jiali Li (Cleaner Logistics and Supply Chain)
The resource and environmental problems caused by excessive packaging of e-tailing goods have attracted widespread attention, and its management has become an urgent task. To this end, we establish a tripartite game model of merchants, logistics enterprises and consumers to analyze the dynamic evolution process of behavioral choices. The results show that (1) the stage of environmental pollution positively promotes the behavioral choices of merchants, logistics enterprises and consumers. (2) Cost expenditures have a greater impact on the evolutionary path of merchants than the benefits generated by excessive packaging of e-tailing goods. (3) Penalties from online platforms have a greater impact on merchants’ evolutionary paths than rewards. This study provides a new perspective for the study of recycling of excessive packaging of e-tailing goods, and the conclusions of the study can provide a reference for governments to formulate effective policies on the management of excessive packaging of goods.